EVALUASI PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN DI ERA REVOLUSI INDUSTRI 4.0 - Mutaqin, Agus Zaenal (Universitas Nurul Jadid, 2020)
Educational evaluation is a process carried out in planning, obtaining, and providing information that is very necessary to make alternative decisions for an activity. The purpose of this study is to explain the quality and effectiveness of the Level IV Leadership education and training. The research method used was to use the qualitative approach of Kirkpatrick Evaluation. The result to be achieved is the availability of leadership training guides that are digitally integrated with all fields, so that the decisions to be taken can be in accordance with the times.